STUDI EVALUASI KELAYAKAN SISTEM INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) RUMAH POTONG HEWAN (RPH) GADANG KABUPATEN MALANG - haribowo, riyanto; sholichin, moh.; yuriski, ryan isra' (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
ABSTRAK: Total limbah yang dihasilkan peternakan dan proses penguraian menjadi faktor dalam kelayakan sistem IPAL. Lokasi studi di Rumah Potong Hewan Gadang, Malang. dengan melihat kandungan BOD, COD, TSS, Minyak&Lemak, NH3-N serta pH pada IPAL serta mengevaluasi kelayakan eksisting IPAL dan prosesnya. Kemudian dibandingkan dengan baku mutu air limbah dalam PermenLH No.02 Tahun 2006. Hasil proyeksi debit 10 tahun kedepan dengan memprediksi efektifitas daya tampung IPAL. Debit yang dihasilkan pada proses pemotongan tersebut sekitar ±158,014 m3/hari dengan jumlah per sapi sekitar 4,515 m3/ekor/hari sebanyak ±35ekor/hari tahun 2017. Setelah pengolahan IPAL, limbah cair menuju sungai yang berada ±200m dari lokasi RPH. Hasil tersebut sebagai acuan untuk 2018-2027, Debit tersebut melebihi batas maksimum dalam Baku Mutu limbah sapi yaitu 1,5 m3/ekor/hari. Pada IPAL terdapat dua parameter diambang batas yaitu Minyak&Lemak dan COD disebabkan parameter yang masih belum terurai. Pada bak pengendap tidak ada alat atau desain guna  mengurangi kadar parameter dan tidak efektifnya bak pemisah lemak. Untuk mengoptimalkan proses pengolahan, kondisi eksisting perlu dilakukan perbaikan atau perluasan pada bak minyak dan lemak agar kinerja bak selanjutnya bekerja maksimal dan mengalihfungsikan bak disinfektan dikarenakan ada bak biofilter yang fungsinya lebih efisien dan tampungan lebih luas.   Kata kunci: Pengolahan IPAL,Pemotongan Hewan,Evaluasi Kelayakan IPAL, Efisiensi Sistem IPALABSTRACT: The total waste generated by the farm and the decomposition process is a factor in the feasibility of the WWTP system. Study locations at Gadang Animal House, Malang. by looking at the content of BOD, COD, TSS, Oil & Fat, NH3-N as well as pH at WWTP as well as evaluating the feasibility of existing WWTP and its process. Then compared with the quality standard of waste water in PermenLH No.02 Year 2006. The result of debit projection 10 years ahead by predicting the effectiveness of the capacity of WWTP. The discharges produced at the cutting process are approximately ± 158,014 m3 / day with the number of cows per 4.515 m3 / head / day as much as ± 35k / d in 2017. After the processing of WWTP, the wastewater into the river is ± 200m from the RPH location. The result is as a reference for 2018-2027, the Debit exceeds the maximum limit in Cash Waste Quality Standard which is 1.5 m3 / head / day. In the IPAL there are two parameters at the boundary that is Oil & Fat and COD due to parameters that still have not decompose. In a sedimentary tub there is no tool or design to reduce the level of parameters and ineffectiveness of the fat separator. To optimize the process of processing, the existing condition needs to be repair or extension on the tub oil and fat for subsequent maximum performance of the tub and disinfectant tube functioning because there is a biofilter tub that function more efficient and wider. Key words: IPAL Processing, Animal Cutting, IPAL Feasibility Evaluation,Efficiency of WWTP                    System  ABSTRACT: The total waste generated by the farm and the decomposition process is a factor in the feasibility of the WWTP system. Study locations at Gadang Animal House, Malang. by looking at the content of BOD, COD, TSS, Oil & Fat, NH3-N as well as pH at WWTP as well as evaluating the feasibility of existing WWTP and its process. Then compared with the quality standard of waste water in PermenLH No.02 Year 2006. The result of debit projection 10 years ahead by predicting the effectiveness of the capacity of WWTP. The discharges produced at the cutting process are approximately ± 158,014 m3 / day with the number of cows per 4.515 m3 / head / day as much as ± 35k / d in 2017. After the processing of WWTP, the wastewater into the river is ± 200m from the RPH location. The result is as a reference for 2018-2027, the Debit exceeds the maximum limit in Cash Waste Quality Standard which is 1.5 m3 / head / day. In the IPAL there are two parameters at the boundary that is Oil & Fat and COD due to parameters that still have not decompose. In a sedimentary tub there is no tool or design to reduce the level of parameters and ineffectiveness of the fat separator. To optimize the process of processing, the existing condition needs to be repair or extension on the tub oil and fat for subsequent maximum performance of the tub and disinfectant tube functioning because there is a biofilter tub that function more efficient and wider.  Key words: IPAL Processing, Animal Cutting, IPAL Feasibility Evaluation,Efficiency of WWTP                     System